ANALISIS PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN DALAM MELAKUKAN SERVIS KENDARAAN (STUDI KASUS DI AHASS ASTRA HONDA MOTOR KEDUNGSARI KOTA MAGELANG) - Achsa, Andhatu; Wibisono, Hamdan Berlian (IMAGE : Jurnal Riset Manajemen, 2020)
AHASS Astra Motor Kedungsari is engaged in vehicle repair services, in addition to genuine parts to meet the need for replacement of vehicle parts that repair damage. Research conducted to analyze the effect of service quality and facilities on consumer satisfaction in conducting vehicle services at AHASS Astra Motor Kedungsari. The data used are primary data using questionnaire distribution techniques and conducting interviews. For this study the sample obtained amounted to 35 respondents, as well as by purposive sampling technique as for the criterion is someone who has serviced vehicles in AHASS Astra Motor Kedungsari, this research was conducted in February 2020. For the data analysis technique using validity, reliability, reliability, classic assumption test and multiple linear regression equations, and data processing using the SPSS version 25 application, the results of data analysis in accordance with the quality of service that consumer satisfaction in AHASS Astra Motor Kedungsari significantly also provides significant consumer satisfaction at AHASS Astra Motor Kedungsari and is related to simultaneous significant variable quality of service and facilities on significant consumer satisfaction at AHASS Asta Motor Kedungsari Magelang.